Migrations, remittances and local development in Southern countries: Dutch disease or residential economy? - Denis Requier-Desjardins (European Regional Science Association (ERSA), 2011)
In developing countries, the contribution of the growing amount of migrant remittances to development remains an unsettled issue. At the macroeconomic level remittances do represent an external flow way above official aid and often in line with FDI. Hence the widely shared optimistic view about this until now "hidden source of development finance". At the microeconomic level remittances raise incomes and have an impact on consumption expenses and therefore on welfare. They can also finance investment in productive assets, such as physical capital and more conspicuously, human capital through education and health expenses. They can therefore improve the resilience of concerned household livelihoods, although it is not granted that remittances necessarily accrue to the poorest households. Remittances on the whole have an impact on poverty abatement but this impact can vary widely. At the meso-economic level relevant data show that migration and remittances concentrate in specific place, raising the issue of their contribution to local development of concerned areas. Concerning the impact of productive investments financed by remittances, picture is rather contrasted with contradictory results from various case-studies. Staying at the meso level, we will compare in this paper two models which have been used, albeit tentatively, to assess the contribution of remittances to local development. - Dutch disease approach, in its sub-national version which features the impact of remittances on real exchange rate. - Residential economy approach which rest on the use of a Keynesian export multiplier applied at an area level to an "economic base" which can be productive but also residential, remittances being considered as a component of this residential basis. These two approaches predict changes in the system of activities due to remittances. However their vision of the consequences of these changes diverge. Their comparative analysis can allow for the identification of key factors of remittance capability to shape a local development path. To achieve that, we shall draw from the huge literature on remittances relating to various countries as well as public statistical data bases.
Keywords: 330